Faktor Eksternal Yang Berhubungan Dengan Minat Ibu Melakukan Kunjungan Ke Posyandu - Juli Widiyanto; Supryati Zebua (Sistem Informasi, 2020)
Posyandu is useful for empowering the community and providing easy access to basic health services. The purpose of this study was to determine external factors related to maternal interest in visiting posyandu (a study in the village of Labuh Baru timur). This type of research is an observational analytic study with a cross-sectional study approach design, namely data collection and results are carried out at one time, the data collection technique is carried out using stratified random sampling where the sample of this study is some of the mothers who have children under five in the village area. Labuh Baru Timur. The instruments used in data collection were questionnaires and analysis used univariate and bivariate with the help of the SPSS Version 16.0 program. The results of research conducted by researchers from March to April 2020 with the title of external factors related to maternal interest in visiting posyandu show that there is no relationship between distance to posyandu, family support, and posyandu service services with maternal interest in visiting posyandu which is proven by p-value> 0.05, which is arranged in sequence 0.931 and OR 1, 046; 0.945 and OR 0.959; 0.768 and OR 0.842. Based on the results of this study, it can be concluded that there is no relationship between distance to posyandu, family support, and posyandu services with mothers' interest in visiting posyandu. It is hoped that mothers in East Labuh Baru Village can further increase visits to posyandu in order to improve the health and development of toddlers.